ANALISIS DAYA SAING DAERAH TUJUAN WISATA UNTUK MENENTUKAN SKALA PRIORITAS PEMBANGUNAN DI JAWA TIMUR (Studi kasus: Kabupaten Jember dan Kabupaten Banyuwangi). - Edi, Bagus Qomaruzzaman Ratu; Rachmawati, Ratih (Relasi : Jurnal Ekonomi, 2018)
Jember Regency of East Java a city with tourist attractions amounted to 44 (fortyfour) and excellent products interesting to know and worth to visit. Jember Fashion Carnaval (JFC); an annual fashion parade event held in Jember, suwar suwir, edamame is popularly known. The competitiveness of tourist destinations using Banyuwangi International Tour de Banyuwangi Ijen, Banyuwangi Batik Festival, and Beach Jazz Festival, also have a new airport (airport) and are in the area most Eastern in East Java. The two districts have many strengths (Strengths) and opportunities (Opportunities) to be developed through the scale of their development priorities. The research was conducted in 2017 in Jember Regency and Banyuwangi Regency of East Java. Objective: To analyze the competitiveness of Jember regency tourist destination, and Banyuwangi, as an effort to know the priority scale of Development in East Java; Determining the position of competitiveness of tourist destinations of Jember Regency compared with Banyuwangi Regency. The result shows that tourism growth in Banyuwangi is bigger than Jember Regency. Meanwhile, price competitiveness indicator price and indicator of openness tends to be constant. Keyword: Jember, Banyuwangi, competitiveness, East Java